Development strategies and support services for SMES : proceedings of four intergovernmental expert meetings (UN New YorkUS, 2000)
Includes papers presented during four intergovernmental expert meetings, held by UNCTAD between 1997 and 1999. Looks at certain critical elements in any SME strategy in four sections of the publication viz. promoting public-private sector dialogue; enhancing interfirm cooperation; developing SME clusters and networks, and providing sustainable services to SMES.
Keywords: SMALL ENTERPRISES